Publicidade e os limites da privacidade: percepção dos usuários a anúncios personalizados - Rosa, Bruna Neder (2022)
The growth of the internet has changed cultural aspects of society with its high power to expand convergence between media fields, in addition to allowing users to become content creators, changing their status as passive receivers, which until then was predominant in the media as a whole and also in advertising. Users started to share various information that are collected through cookies, which are files that store user information not only to make a more qualified browsing experience, but are also marketed by Data Brokers, companies that have data from various commercial, government and public sources that collect and categorize them all, creating audiences to be used in advertising with the aim of reaching users that are most likely to purchase a particular product or service. Increased surveillance has also generated discussions about data privacy and encouraged the creation of new laws such as the LGPD (Lei Geral de Proteção de Dados or General Data Protection Regulation), which addresses the transparency of these companies in data collection, but not how society deals with this surveillance. Therefore, this dissertation aims to understand the perceptions of users regarding personalized ads in online advertising